EFFECTIVENESS OF LEARNING THROUGH VIDEO CLIPS AND VIDEO LEARNING IMPROVEMENTS BETWEEN BUSINESS RELATED POSTGRADUATE AND UNDERGRADUATE STUDENTS - Dominic Wong (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Learning is important for students to build their foundation of knowledge that they can utilize in their future careers. Learning through videos is considered an effective tool for many students, the topic was well-reviewed by many researchers. This paper is going to explore the learning effectiveness of video in teaching business-related topics and will also include suggestions to improve teaching using video clips. The researcher is using Google Form survey as the main tool for data collection, simple descriptive statistics and T-Tests are used in this research. Indeed, the results show that learning through video is perceived as effective by students. A simple comparison between postgraduate and undergraduate students’ perceptions towards the learning effectiveness and improvements is also conducted in which they are indifferent in most variables.